The Entrepreneurial Network of Muslim Women Entrepreneurs: The Study of Multiple-Cases of Small Businesses in the Southern Region of Malaysia - Omar, Siti Sarah (International Journal of Economics and Financial Issues, 2015)
This paper seeks to empirically explore the dynamics roles of strong and weak ties within Muslim female entrepreneurs' networks during critical problems (“tipping points”), and how this affects the subsequent performance of the small businesses. The literature review shows that many studies have explored the mix of strong and weak ties in small businesses linking them to stages of business development. More recent literature, however, has conceptualized firm growth through the notion of critical problems or “tipping points” that must be successfully tackled in order to continue on a development path. While the importance of network ties has been well documented in relation to growth stages, limited work has investigated the contribution that strong and weak ties make as a firm faces specific “tipping points,” thus showing a call for further investigation. This is a qualitative study involving four cases of small-sized food manufacturing firms in the Southern region of Malaysia. The main data collection method is an in-depth interview with the owner-managers using critical incident interview technique. The triangulation of data has been carried out by interviewing individuals who are seen as strong and weak ties of the network. They suggest that the dynamics roles of strong and weak ties are essential during the “tipping points.” The findings have implications for firms, networks and the government. It also provides a detailed understanding on the nature of entrepreneurial network of entrepreneurs in Malaysia. Recommendations are presented that address the need to support small businesses in dealing with critical problems in relation to their networking practices. Keywords: Social Network; Network Ties; Growth; Tipping Points; Small Businesses JEL Classifications: M00